(untitled) (Third Sector Social Economic Review, 2023)
The purpose of this study is to examine the moderating effect of political skill on the relationship between job crafting and work engagement. Job crafting, work engagement and political skill levels of employees stand out as important factors in human resources planning of organizations in today’s increasingly competitive world. Job crafting is the ability of individuals to fulfill their duties and be successful in their jobs. This resourcefulness is related to an individual’s technical knowledge and experience as well as general skills such as communication and problem solving, as well as the ability to learn and adapt. Job crafting is important because it has a direct impact on concepts such as individuals’ performance, productivity, commitment and job satisfaction. Work engagement, another factor that has an impact on organizational success, depends on personality traits such as job crafting, resourcefulness and motivation. In addition, organizational policies can play a role in the retention process; internal conflicts or individual connections can affect the organization. Political skill, which is one of the important concepts in terms of career development and promotion progression of individuals, is the individual’s ability to establish social relationships, gain power and influence other individuals in the organization. In working life, being successful depends not only on job crafting and work engagement, but also on political skill, which is defined as the ability to establish and manage effective relationships in the work environment and to use social networks effectively. Within the scope of this study, it is thought that understanding how the concepts of job crafting, work engagement and political skill are related to each other is an important research topic for both organizations and individuals. The sample of the study consists of 222 graduate students studying at Aksaray University Institute of Social Sciences in the 2022-2023 academic year and working in the public sector. When the literature is examined, although there are a few studies investigating the relationship between job crafting and work engagement, there is no study that deals with the regulatory effect of political skill in this relationship. SPSS 26, AMOS 24 and PROCESS Macro V4.1 programs were used in the research analysis. According to the research findings, positive and significant relationships were found between job crafting and its sub-dimensions of task, cognitive and relational resourcefulness and work engagement. In addition, it was concluded that political ability has a moderating effect on the relationship between job crafting and work engagement. Within the scope of this study, first of all, the existing studies in the literature on job crafting, work engagement and political skill were examined and it was aimed to contribute to the literature on this subject by creating an applied study based on this information.